Dispersion of nanoparticles in optically transparent polymer matrices - Borshchov, V.M.; Listratenko, O.M.; Protsenko, M.A.; Tymchuk, I.T.; Kravchenko, O.V.; Syddia, O.V.; Slipchenko, M.I.; Chichkov, B.M. (Radiotekhnika, 2021)
Search and analysis of results of theoretical and experimental studies, materials of dissertations, literature sources and patents in the field of optical and optoelectronic instrumentation were carried out. Obtained data and recommendations on the development of methods for dispersing nanoparticles into polymer matrices for the creation of optically transparent nan composites for use in many fields of science and technology are generalized. Analysis of considered results makes it possible to conclude that for creating hybrid organic-inorganic composites with high level of dispersion of inorganic component, it is necessary to solve problems relating to compatibility of components and stabilization of filler nanoparticles in polymer matrix. Due to the limited range of hydrophilic polymers capable of forming composites with nanoparticles without stabilizers, the main approaches to the preparation of hybrid composites are using modifying additives of surfactants, as well as complex chemical reactions on the surface of inorganic filler nanoparticles. Such methods of obtaining nanocomposites with nanoparticles are laborious and involve formation of by-products and additional purification. It is shown that titanium dioxide (TiO2) and zinc oxide (ZnO) are of great interest among a large number of nanodispersed fillers of polymer matrices in preparing composite materials. There are many methods for synthesis of ZnO and TiO2 nanoparticles with various shapes and sizes, including laser ablation method, which is convenient and universal method for preparing nanosuspensions of solid-phase materials in liquid. Advantages over other methods for nanoparticle synthesis, such as the simplicity of method, environmental friendliness, low cost, and the ability to obtain cleaner colloidal solutions without using surfactants and other impurities, have made laser ablation in a liquid medium very popular among researchers.